2018
DOI: 10.5194/aab-61-373-2018
|View full text |Cite
|
Sign up to set email alerts
|

Digestive tract morphometry and breast muscle microstructure in spent breeder ducks maintainedin a conservation programme of genetic resources

Abstract: Abstract. The objective of this study was to compare three genetic groups of ducks: P9 (French Pekin), K2 (bred from wild mallards – Anas platyrhynchos L. and Pekin duck), and KhO1 (hybrid of Khaki Campbell drake and Orpington Fauve duck) after two breeding seasons for body weight and length, length of intestine and its segments, percentage of other internal organs, and breast muscle microstructure. The study used 60 ducks, 20 birds (10 males and 10 females) from each genetic group. At 110 weeks of age, P9 duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…The effect of sex and the genotype by sex interaction for the microstructural traits of pectoralis major muscle of the analyzed ducks were not confirmed statistically ( Table 7 ). Kokoszynski et al. (2018) observed no significant differences between 110-week-old P9 (French Pekin), K2 (bred from wild mallards– A. platyrhynchos L. and Pekin ducks), and KhO1 ducks (hybrid of Khaki Campbell drake and Orpington Fauve duck) after 2 reproductive seasons in fiber cross-sectional area, fiber perimeter, and fiber vertical diameter, which is contrary to the results of the present experiment.…”
Section: Resultscontrasting
confidence: 99%
“…The effect of sex and the genotype by sex interaction for the microstructural traits of pectoralis major muscle of the analyzed ducks were not confirmed statistically ( Table 7 ). Kokoszynski et al. (2018) observed no significant differences between 110-week-old P9 (French Pekin), K2 (bred from wild mallards– A. platyrhynchos L. and Pekin ducks), and KhO1 ducks (hybrid of Khaki Campbell drake and Orpington Fauve duck) after 2 reproductive seasons in fiber cross-sectional area, fiber perimeter, and fiber vertical diameter, which is contrary to the results of the present experiment.…”
Section: Resultscontrasting
confidence: 99%
“…For example, the CSA of muscle fibres in F. limosus (85.04 μm 2 ) is four times smaller than that in horseshoe crab, Limulus polyphemus —484 μm 2 [ 114 ]. Even greater differences in fibre size were observed when comparing crayfish meat to that of various fish species—sea bass [ 115 ], common carp [ 100 ], tench [ 116 ], as well as livestock—pork [ 103 , 104 ], beef [ 117 ], chicken [ 118 ], and duck [ 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the CSA of muscle fibres in F. limosus (85.04 µm 2 ) is four times smaller than that in horseshoe crab, Limulus polyphemus-484 µm 2 [114]. Even greater differences in fibre size were observed when comparing crayfish meat to that of various fish species-sea bass [115], common carp [100], tench [116], as well as livestock-pork [103,104], beef [117], chicken [118], and duck [119]. Some of the most important sensory properties of the meat of aquatic animals are the intensive odour and flavour (fishy, seaweed), which depend particularly on storage conditions [120].…”
Section: Culinary Properties Of Spiny-cheek Crayfish Meatmentioning
confidence: 98%
“…Furthermore, this experiment [36] did not confirm a significant effect of sex on caeca length observed in our study. Kokoszyński et al [38], who evaluated P9 Pekin ducks after two reproductive seasons, observed that individual intestine segments were longer except for duodenum when compared to P9 ducks evaluated at 49 d. It was also found that the compared lines of P8, P9 and P33 ducks had lower diameters of duodenum, jejunum, ileum, caeca and colon when compared with the diameters of intestinal segments in commercial hybrids of Pekin ducks (SM3 Heavy or AF51) [37]. The differences in intestinal length and diameter have an effect on the intestinal villus area and nutrient absorption, which influences productive traits in poultry.…”
Section: Discussionmentioning
confidence: 99%